The clinical elective course and its effects on medical students and graduates of Jordanian medical schools - Raed Al-Taher; Ruba Al-Ani; Abdullah Al-Ani; Mohammad Rashdan; Abdel rahman A. Al Manasra; Emad Aborajooh; Hamzeh Al-Balas; Hasan Al-Balas; Mahmoud Al-Balas; Maymoona Attiyat; Nuha Qasem (BMC Medical Education, 2022)
Abstract Background The elective course is part of the 6th-year medical school curriculum in Jordan. Students choose the specialty in which they wish to spend 8 weeks and choose their location even if it is outside their university’s affiliated hospitals. In this study, we try to understand student choices regarding the country of elective, chosen specialty, type of placement (observership/clerkship), and elective general value from participants' perspectives. Methods This paper used a cross-sectional study. The survey was distributed through social media platforms (mainly Facebook and WhatsApp) targeting 6th-year medical students and doctors who graduated from one of the 5 Jordanian medical schools (the University of Jordan, Jordan University of Science and Technology, Mutah University, Yarmouk University, and Hashemite University). Results The majority of participants had an international elective (69.6%), mainly in the USA, followed by the UK. Internal medicine was the primary field of interest for 14.8%, followed by general surgery. Of these, 241 (62.6%) actively participated in work at their chosen hospitals as they had a clerkship/hands-on experience. In contrast, 142 (36.9%) were observers. The majority indicated that the elective is worth the time, money, and effort. Moreover, they had adequate supervision throughout the course and could achieve their preset objectives. Conclusions The elective course gives a unique experience to our students. General satisfaction is an indicator of the success of the course in actively exposing medical students to clinical practice.